Gagnasett: Útbreiðsla hæruburstar Campylopus introflexus (Hedw.) Brid. á Íslandi - lokaskýrsla. - Wasowicz, Pawel; Vilmundardóttir, Olga Kolbrún (Zenodo, 2024)
This is the data collected in 2023 and 2024 during the research on the distribution of Campylopus introflexus in geothermal areas in Iceland